2020
DOI: 10.3390/polym12102336
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complex of Docetaxel with Sulfobutyl Ether β-Cyclodextrin: Preparation, In Vitro Cytotoxicity and In Vivo Safety

Abstract: Docetaxel (DTX), as a first-line anti-tumor drug, has been studied for decades for its diverse bioactivities. However, DTX presents poor solubility in water, low bioavailability and serious toxic side effects which has hindered its application in the clinic. To address these problems, docetaxel-sulfobutyl ether-β-cyclodextrin inclusion complex (DTX-SBE-β-CD) was prepared successfully by saturated aqueous solution method. Sulfobutyl ether β-cyclodetrin (SBE-β-CD) is used as delivery material. For this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Hemolysis, liver damage, renal damage status in blood and histological data are used to evaluate the safety of polymers. The inclusion complex of SBE βCD prepared with docetaxel was found to be safer than free docetaxel in the hemolysis and vascular stimulation test in rabbits [ 50 ]. When the implant containing poly-HPβCD and ropivacaine was examined in the rat, no negative effects were observed in the samples and histopathological data [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis, liver damage, renal damage status in blood and histological data are used to evaluate the safety of polymers. The inclusion complex of SBE βCD prepared with docetaxel was found to be safer than free docetaxel in the hemolysis and vascular stimulation test in rabbits [ 50 ]. When the implant containing poly-HPβCD and ropivacaine was examined in the rat, no negative effects were observed in the samples and histopathological data [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be stated that β-CD is efficient in improving the solubility of docetaxel. An earlier complexation study performed using sulfobutyl ether β-cyclodextrin showed that docetaxel also formed a stable inclusion complex with it, which also showcased a magnificent increase in water solubility (Ren et al, 2020). This solubility has been further enhanced by the addition of the hydrophilic polymer.…”
Section: Phase Solubility Analysismentioning
confidence: 95%
“…Following the previous study, we used the saturated aqueous solution method to prepare the β-CD-CHX. The β-CD was dissolved in double-distilled water and the CHX in ethanol, and the molecular molar ratio of β-CD to CHX was 1:1. , The next step is the preparation of scaffolds. First, CAD software was used to design the scaffold material.…”
Section: Methodsmentioning
confidence: 99%